PERDUKUNAN, SIHIR, DAN RAGAMNYA: SEBUAH UPAYA UNTUK MEMAHAMI PRAKTIK RAHASIA DALAM NARASI-NARASI KISAH PARA RASUL - Claudie Valda Silooy (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
This article will discuss shamanic practices still preserved today by people in Indonesia. In general, this paper will examine the variety of definitions that existed long before the practice of shamanism. Specifically, it will discuss the sources of knowledge, their functions and uses in shamanic practice. It will then show the critical theological attitude that is a significant part of today's Christians by using some of the narratives in Acts 8, 13, and 19. The characters in the narrative of Acts 8, 13, and 19 will be dissected using Andy Reimer's theory of the perspective embodied in the definition of magic. This paper uses qualitative research methods from books, scientific journal articles, and internet articles to obtain helpful knowledge. This method gives birth to several main points: 1) God has absolute power, while man is only a finite being; 2) The powers of darkness cannot compete with God's miracles; 3) God's consecration and protection are bestowed upon man through the celebration of the Lord's Supper as a form of miracles that can be used for all time; 4) Holy Communion is a healing process that man can use to ward off magical powers.